The effect of interaction between the inverted classroom through mobile applications and the cognitive approach in developing communication skills in mathematics among middle school students - Al Rahili, Nargis Salem Salameh (Journal of Educational and Psychological Sciences, 2018)
The study aimed to measure the effect of the interaction between the flipped classroom through Telegram application and the cognitive method (independent-dependent) on the cognitive field in the development of mathematical communication skills (reading, writing, representation) among intermediate school students. The researcher followed the descriptive approach and the semi-experimental approach based on experimental design based which is based on the two experimental groups. The research tool was designed to test the skills of mathematical communication. The study sample which consisted of (60) grade 8 students. They were divided into two groups according to the cognitive style (independent-dependent) from the cognitive domain and They were taught in an flipped classroom way using Telegram application. The results of the study showed that there were statistically significant differences at the level of (0.05) between the average scores of the students of the experimental groups in the prior and post application to test the skills of mathematical communication, where the independent method group obtained average 3.88 in the prior while in the post the average was 11.67, also the dependent method group obtained in the prior average 3.23 and in the post obtained average 10.75. which prove that the interaction between the flipped classroom through Telegram application and the cognitive method (dependent & independent) led to huge impact in improving the mathematical communication skills on the study sample. The study recommendations are: encouraging teachers on the use of flipped classroom way through training and workshops in manner that develop the motivation of the learner orientation towards mathematics, also to take advantage of the outcome of this study in scientific research.
Keywords: Flipped class; sports communication skills; cognitive style (dependent - independent)